Overcoming test anxiety: perspectives of senior students of the Faculty of Education - Abdul Raof, Abdul Halim; Ab. Nasir, Nurul Hana (2010)
This study set out to investigate ways to overcome test anxiety from the perspectives of senior students of the Faculty of Education. Test anxiety as Zeidner defined it and quoted by Cizek and Burg (2006) is uneasiness feelings towards things that have to do with evaluative situation. The study which took place in UTM, Skudai aimed to look for expressions and sources of test anxiety as perceived by UTM senior students. It also aimed to find out how they overcome it. A set of questionnaires was distributed to 91 students from SPM 3112 course, Programming Language II. Nine of the respondents agreed to participate in a semi- structured interview. The overall results showed that senior students of UTM expressed their test anxiety through thought disruption and they felt anxious because they were concerned about their preparation for test. It was found that most participants perceived test anxiety as a normal feeling and thus, not many were bothered to overcome it. However, it was found out too that there were two ways that participants overcome test anxiety. These can be categorised as physical reactions and mental reactions. The mental reactions are further divided into two which are self-motivation and religious belief. It is hoped that this study will give benefits to both students and lecturers of the Faculty of Education, in particular, on the issues of test anxiety.